Analysis of the Growth Rate and Effectiveness of Advertisement Tax Revenue on Original Regional Income in Kupang City - Bhetrix Adriani Widhia Amung; Nikson Tameno; Cicilia A. Tungga (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine and explain the growth rate and effectiveness of advertising taxes on local revenue in Kupang City in 2017-2021. This research uses a qualitative descriptive approach. This research uses growth rate analysis by comparing the realization of regional revenues in a particular year and the realization of regional revenues in the previous year. The effectiveness of advertising tax is measured by comparing the realization and target of advertising tax revenue. The research results show that the growth rate of advertising tax revenue has fluctuated from 2017-2021 with an average of 8.73%. This shows that the growth of advertising tax revenue in Kupang City has not been successful. The effectiveness of advertising tax in Kupang City in 2017-2021 with an average of 93.94% is included in the effective category. For this reason, it is recommended that the government and the public, especially taxpayers, work together to increase revenue from the advertising tax sector in order to increase Original Regional Income